Passing differences between winning and losing teams in the National Hockey League (NHL) - Franjkovic, A.; Matkovic, B.; Vlahovic, T. (10th International scientific conference on kinesiology. Book of abstracts, 2024)
Ice hockey is a highly popular winter Olympic sport that reqiures significant increase in the use of sport analytics. Elite ice hockey players need to have well-rounded physical and physiological capabilities including aerobic and anaerobic fitness, muscular strength, power, and endurance. These physiological qualities are expressed in ice hockey by combining dynamic skating movement patterns with skills such as shooting, passing of the puck, and evading defenders. The sample was collected by analyzing 20 randomly selected matches from the NHL With use of notational analysis. 8533 phases of attack were extracted from the selected matches of the National Hockey League. T-test shows that there is statistically significant difference between winning and losing teams (1,809 ± 1,66 and 2,012 ± 1,83, respectively) with T-value = - 5,3308 with 95% confidence p = 0,0000. The most differences make variables Giveaway and Attempt shot